Linkage Between Mangrove Seedling Colonization, Sediment Traits, and Nitrogen Input - He, Ziying; Yen, Lingwei; Huang, Hongjie; Wang, Zihao; Zhao, Lili; Chen, Zhonghan; Lee, Shing Yip; Peng, Yisheng (Frontiers in Marine Science, 2022)
Mangroves settle along coasts and estuaries where usually encounter the influence of aquaculture effluent that renders eutrophication and regulates the nitrogen cycle in mangrove ecosystems in the world. Moreover, along with the increasing occurrence of extreme climatic events, the physical-chemical features of sediment in mangrove habitats might be altered by coastal wind, wave, and current more frequently. Besides, the degradation and loss of mangroves will impair their capacity of sediment capture and the process of colonization/regeneration. To study how exogenous nitrogen input and sediment physical-chemical features affected the root system establishment of mangrove propagules, and early growth of seedlings in turn, we set up a mesocosm experiment to explore the morphological and physiological responses of the root system of two mangroves, i.e. Kandelia obovata and Sonneratia apetala. We found that the root morphological features of mangrove seedlings mostly showed significant differences across the treatments of sediment types, especially the K. obovata seedlings were more intensively influenced than S. apetala. It could be ascribed the root of K. obovata seedling was more sensitive to sediment types than that of S. apetala seedling. Reversely, the treatment of exogenous nitrogen input showed a slighter or non-significant influence on root features of mangrove seedlings. In terms of adaptability to nitrogen input and sediment types, the seedlings of S. apetala exhibited higher ability than those of K. obovata. In estuaries and coasts featured by eutrophicated and various sediment types, the exotic S. apetala might outcompete the native K. obovata with respect to the seedlings colonization and establishment. Therefore, we suggest restricting the extent of plantations dominated by S. apetala, and control or remove the natural colonizing population of S. apetala to facilitate the natural/artificial restoration of native mangroves.